From unemployment to disability? Relationship between unemployment rate and new disability pensions in Iceland 1992-2007 - Thorlacius, Sigurður; Ólafsson, Stefán (The European Journal of Public Health, 2012)
Background: The study was carried out in order to examine the effect of unemployment on the incidence of disability pension in Iceland by examining changes in this relationship from 1992 to 2007. Methods: The annual incidence of disability pension for the period 1992–2007 was calculated. Correlations and significance tests for the relationship between unemployment rates and disability pension incidence rates were calculated. The relationship was examined for different disease groups. Results: Two big fluctuations occurred in the unemployment rate during the study period with an upswing in unemployment from 1993 to 1995 and in 2002 and 2003. In both cases, there were corresponding increases in the incidence of disability pension. The incidence of disability pension declined again when the level of unemployment went down, even though not to the same extent. Conclusions: Health and mental and physical capability determine the overall incidence of disability pension, but marginal fluctuations over time seem to be related to environmental conditions in the labour market, especially the unemployment rate. The observed disability pension incidence pattern in the two unemployment cycles of the study period indicates mainly that people with impaired health are forced out of the labour market in times of increasing unemployment rather than pointing towards a negative effect of unemployment on health. Our findings indicate that there is a need to strengthen the vocational rehabilitation system in Iceland as well as the support system for employment and social participation.